Is high socioeconomic status a risk factor for multiple sclerosis? A systematic review. (5th November 2014) - Goulden, R.; Ibrahim, T.; Wolfson, C.
<x xml:space="preserve">Abstract</x> High socioeconomic status (SES) is generally associated with better health outcomes, but some research has linked it with an increased risk of multiple sclerosis (MS). The evidence for this association is inconsistent and has not previously been systematically reviewed. A systematic review of cohort and case–control studies in any language was conducted looking at the association between MS and SES. MEDLINE and EMBASE were searched for articles in all languages published up until 23 August 2013. Twenty‐one studies from 13 countries were included in the review. Heterogeneity of study settings precluded carrying out a meta‐analysis, and a qualitative synthesis was performed instead. Five studies, all from more unequal countries, reported an association between high SES and MS. Thirteen studies reported no evidence of an association, and three studies reported an association with low SES. These 16 studies largely came from more egalitarian countries. The evidence for an association between high SES and increased MS risk is inconsistent but with some indication of a stronger effect in countries and time periods with higher inequality. Firm conclusions are hampered by the failure of most studies to control for other important risk factors for MS.